Parkes Weber Syndrome - Szeliga, Adrianna; Spyt, Dominika; Maćków, Ewelina; Kasinowicz, Mateusz (Journal of Education, Health and Sport, 2019)
Introduction: Parkes Weber Syndrome (PWS) is a traditional eponymous denomination of a certain type of angiodysplasia. It is a congenital vascular disease which consists of capillary malformation (CM), venous malformation (VM), lymphatic malformation (LM), congenital arteriovenous malformation (AVM) and multiple arteriovenous fistulas (AVFs). There is a soft-tissue and skeletal hypertrophy of the affected extremity (usually a lower extremity). Moreover the affected limb is warmer and longer than the other side. Objective: The aim of this article is to summarize the current state of knowledge about Parkes Weber Syndrome: the pathophysiology, genetic inheritance, the main symptoms, the diagnosis especially differential diagnosis and the current treatment. Brief descriptions of the state of knowledge: Despite many years, physicians still have difficulties with diagnosing PWS correctly. Although the aetiology is unknown, it is claimed that PWS is caused by mutations of the RASA1, gene located on chromosome 5q13.1, which are inherited in an autosomal dominant manner. This gene is responsible for mediating cellular growth, differentiation and proliferation. No efficacious pharmacological treatment has been found. Nowadays Tranexamic Acid, Sirolimus, Everolimus and Miconazole are used in medical practice. The most frequently utilized invasive treatment methods are amputation, surgical AVM resection and occasionally stent-graft implantation. Furthermore it is thought that embolization, alone or combined with surgical resection leads to clinical improvement. Summary: Despite the existence of many clinical trials, long term observations and scientific speculations, PWS can still be challenging for clinicians. There is a need for further scientific, molecular and genetic research to diagnose this phenomenon correctly, because despite fact, that its symptoms are similar to other syndromes or entities, therapeutic strategies differ significantly. It is important to increase the awareness of inheritance in an autosomal dominant manner in generation of patients with PWS.